A bibliometric retrospection of marketing from the lens of psychology: Insights from Psychology & Marketing. Issue 5 (10th March 2021) - Donthu, Naveen; Kumar, Satish; Pattnaik, Debidutta; Lim, Weng M.
Abstract: The contribution of psychology to marketing has been significant and invaluable. No discipline has benefitted from another as much as marketing from psychology. To gain an understanding of the scientific contributions emerging from the intersection of psychology and marketing, this study conducts a bibliometric retrospection of a premier journal dedicated to the application of psychological theories and techniques to marketing: Psychology & Marketing ( P&M ). To do so, this study employs bibliometrics to unpack the publication trends and the intellectual structure of P&M . In doing so, this study reveals several interesting findings. First, P&M 's publications grew by 71.9 times, authorships grew by 82.1 times, and citations grew by 150.8 times between 1984 and 2020, indicating a healthy growth of marketing research informed by psychology. Second, P&M 's contributions manifest through eight intellectual clusters—namely, marketing environment; consumer engagement; online consumer behavior and marketing; luxury consumption and marketing; sustainable consumption and marketing; influencer and international marketing; customer relationship, satisfaction, and loyalty; and marketing futures. Finally, P&M 's emerging and promising areas for future exploration include aesthetics and consumer impressions; celebrity endorsement; conspicuous consumption and hedonic adaptation; climate change; choice likelihood; consumer engagement; consumer psychology; marketing communication; sensory marketing; sharing economy; and social media marketing. As a whole, these findings should provide readers with a state‐of‐the‐art overview of marketing from psychology through the scientific contributions from P&M .